The sable for Evenk reindeer herders in southeastern Siberia: interplaying drivers of changes on biodiversity and ecosystem services - climate change, worldwide market economy, and extractive industries - Lavrillier, Alexandra; Gabyshev, Semen; Rojo, Maxence (UNESCO, 2017)
Includes bibliography